Aplikasi Pengolahan Rumput Laut Berbasis Web - Mustari, Mutrafin; Marlina, Marlina (Jurnal Sintaks Logika, 2024)
The seaweed processing industry is a promising sector with significant economic growth potential. In this context, developing a web-based application to facilitate seaweed processing can be a strategic step and optimize the processing process, facilitating inventory management, production monitoring, market analysis. The aim of this research is to develop seaweed processing applications and industrial services. The method used was a quantitative method for one month in Pinrang Regency. This application was built using Visual Studio Code, XAMPP, and also MySQL as the database and PHP programming language. The results of this application can make it easier for seaweed farmers to get the latest information on cultivation, input data on production results, and sales reports that can be seen by other employees.